Spectrum of spontaneous photon emission as a promising biophysical indicator for breast cancer research. Issue 1 (December 2017) - Zhao, Xiaolei; Yang, Meina; Wang, Yong; Pang, Jingxiang; Wijk, Eduard; Liu, Yanli; Fan, Hua; Zhang, Liewei; Han, Jinxiang
Abstract In this study, we investigated the spectral characteristics of Spontaneous Photon Emission (SPE) from the body surface of a human breast cancer-bearing nude mice model during the overall growth process of breast cancers. By comparing and analyzing the data, we found that there was a striking difference between tumor mice and healthy controls in the spectral distribution of SPE from the body surface of lesion site, even when the morphological changes at the lesion site were not obvious. The spectral distribution of SPE from the healthy site of the tumor mice also differed from that of the healthy controls as the breast cancer developed to a certain stage. In addition, the difference in spectrum was related with different growth states of tumors. Interestingly, there was a positive correlation between the spectral ratio (610–630/395–455 nm) and the logarithm of the tumor volume for both the lesion site (R2  = 0.947;p  < 0.001) and the normal site (R2  = 0.892;p  < 0.001) of the tumor mice. The results suggested that the spectrum of SPE was sensitive to changes in the tumor status.